Analisis Kestabilan Lereng Menggunakan Metode Bishop di Pit ALC-14 Tambang Batubara PT. Equalindo Makmur Alam Sejahtera Kabupaten Kutai Kartanegara, Kalimantan Timur - Saldi Muhammad; Masri Masri; Hasria Hasria (Jurnal Geomine, 2020)
The coal mining, especially at the production stage, must pay attention to the slope stability. This study aims to determine the factor of safety (FoS) of the mine slope with the limit equilibrium method. This analysis also includes the influence of the slope geometry, physical and mechanical properties of the slope materials of PT. Equalindo Makmur Alam Sejahtera, East Kalimantan. The limit equilibrium method used is the Bishop Method, which uses the principle of moment equilibrium by calculating the normal force between slices. The geomorphology unit classified as hilly units with 70% angle of slope face, composed by sandstone and claystone intercalations with coal. The results of the analysis show the stability level of lowwall, and highwall slopes are quite varied with low FoS values found on the lowwall, such as the slopes in the incision B-B 'and C-C'. The slip failure on the unstable slope is in the contact area between sandstone and claystone, although single slope analysis also shows the slip failure in the form of claystone and coal contact. The low FoS value on the lowwall slope is influenced by the dip of the rock layer in the parallel direction of the slope face, supported by the higher slope face angle of the overall-slope on the lowwall, and the lower internal friction angle in the claystone. The slope design recommendations are carried out by re-sloping and enlarging the width of the bench. The presence of tension cracks and mud cracks on unstable slope faces shows the need for slope monitoring.